Structural analysis of peptides that interact with Newcastle disease virus - Chia, Suet Lin; Tan, Wen Siang; Jois, Seetharama D.S.; Shaari, Khozirah; Yusoff, Khatijah (Penerbit Universiti Sains Malaysia, 2004)
Newcastle disease virus is a negativepolarity, single-stranded RNA virus (Lamb and Kolakofsky, 1996). It causes an economically important disease called Newcastle disease.